A study on postnatal evaluation and follow-up of infants with antenatally detected hydronephrosis - Balasankar, Soundaiyan; Balasubramanian, Jeyaraman (International Journal of Contemporary Pediatrics, 2017)
Background: Antenatal hydronephrosis(ANH) has now become a frequent diagnosis with the increasing use of antenatal ultrasonography. Objective of present study was to evaluate and follow up infants with antenatally detected hydronephrosis and to determine whether there is significant correlation between anteroposterior renal pelvic diameter detected in antenatal USG and urinary tract anomalies detected postnatally. Methods: After obtaining an informed consent, all neonates with antenatal ultrasound showing hydronephrosis (n=80) were enrolled in the study. Postnatal ultrasound was done at 3 days ,1 month and 6 months of postnatal life. Atleast 6 months followup was done to look for spontaneous resolution or other significant pathology. Micturating cystourethrography/radionuclide scan done in selected cases. Results: Out of 80 cases ,43 had mild,24 had moderate and 13 had severe degrees of hydronephrosis.31 of them (9 mild,10 moderate and 12 with severe hydronephrosis) had postnatal anomaly detected.14 of them (1 mild, 4 moderate and 9 with severe hydronephrosis) underwent surgery. As the grade of antenatal hydronephrosis increases from mild, moderate to severe, the relative risk of postnatal anomaly and requirement of surgical intervention also increased (p value<0.0001). Conclusions: Antenatal hydronephrosis may be associated with significant postnatal urinary tract anomaly with risk quantified by the measurement of anteroposterior renal pelvic diameter(APPD).